Developing and Validating a Measurement Scale for Perceived Value of Couchsurfing Experience in Tourism Industry: Implications for Rural Development - Abu Elnasr E. Sobaih; Hassane Gharbi; Samar Zgolli; Imed Zaiem (Economies)
Couchsurfing, a non-commercial form of accommodation, has become a way of life for travellers who want to open to other cultures and exchange with the inhabitants of the countries or regions they are visiting in a more active and authentic way. Despite the growing number of studies on couchsurfing recently, there is not to date an instrument for understanding the perceived value and experience of those travellers. This research fills a gap in research on the couchsurfing phenomenon by developing and validating a scale to assess the perceived value of a couchsurfing experience. The research adopted a mixed-method approach through qualitative and quantitative phases of studies. Both phases were undertaken with couchsurfers who had recently engaged in a couchsurfing experience. The results enabled us to obtain a reliable and valid scale for measuring the perceived value of a couchsurfing experience with three dimensions and nine items measuring economic value, exploration value and socio-cultural value. The measure could be used by service providers to develop appropriate tourism experiences, which impacts tourism development, particularly in rural areas.